Ökonomie des Teilens - nachhaltig und innovativ? - Theresia Theurl; Justus Haucap; Vera Demary; Birger P. Priddat; Niko Paech (Wirtschaftsdienst, 2015)
Die Sharing Economy hat sich durch die neuen Kommunikationsmöglichkeiten aus der Nische in die Mitte der Ökonomie katapultiert. Dabei betrifft das Phänomen sehr unterschiedliche Marktbereiche: vom altruistisch motivierten Teilen unter Freunden und Nachbarn bis zu kommerziellen Dienstleistungsangeboten. Die Sharing Economy ist mit der Hoffnung verbunden, bestehende Kapazitäten besser auszulasten und entsprechend ressourcenschonend zu wirken. Wird Eigentum geteilt, können allerdings Organisationsrenten abgeschöpft werden. Wer davon profitieren sollte, ist zu diskutieren. Die Debatte zum Taxidienstleister Uber hat zudem die Bedeutung des Regulierungsrahmens deutlich werden lassen. – – The sharing economy is spreading increasingly throughout the traditional economy. By means of innovative information technology, this business model generates effective concepts to reduce transaction costs and other barriers which hinder businesses that sell services instead of material goods. There are great expectations that the new market structure might save resources, but these may be fallacious. Sharing models may increase external costs, since these concepts foster unsustainable lifestyles and other financial rebound effects. The sharing economy comprises numerous different business models whose common trait is that the emphasis is placed not on ownership but rather on the use of a good. While the sharing economy's encroachment into providing taxi services has proven to be especially contentious, the fact that the sharing economy's business models are heterogeneous means that market regulation should be examined market by market to ensure fair competition between traditional and non-traditional firms. The governance structures of the sharing economy, as they are practiced today, imply that it is mainly the platform owners who absorb all the profits. In contrast, a sharing economy using cooperatives as an organisational vehicle ought to direct profits to users instead of investors.
Keywords: D47; L14; L23; 330; Share Economy; Geschäftsmodell; Rent-Seeking; Regulierung; Governance-Ansatz; Wirtschaftswachstum; Kritik